The taxonomy of the Southern African species of the genus Cicadulina China (Homoptera : Cicadellidae), with remarks on the economic importance and ecology of the maize leafhopper, Cicadulina mbila (Naude), a vector of maize streak disease - Van Rensburg, George Diederick Janse (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. (Agric.)) -- University of Stellenbosch, 1980.